Dramaturgy for the puppet theatre yesterday and today - McCormick, John (Dramaturgias, 2021)
Until the twentieth century notions of dramaturgy were closely bound up with the Poetics of Aristotle, often leaving out of account less ‘regular’ forms from Shakespeare to the melodrama. From the 17th to the 19th century live actors and puppets could be virtually interchangeable, performing the same or similar repertoires. Adaptation of plays from the actors’ theatre was the general rule. Comparatively few authors wrote directly for the puppet stage, and when they did it was usually under special circumstances. In the nineteenth century a juvenile market began to grow, Two main streams in European puppet theatre are: 1. puppets used in conjunction with story-telling and 2. puppets as substitutes for the live actor. The fact that the puppet is usually a small humanoid figure means that it has always been a valuable vehicle for parody and satire. The theatrical avant-garde that came onto existence in the late 19th century had an enormous impact on puppetry and the direct links between the puppet and the human began to disappear. Gordon Craig’s idea of the complete man of the theatre, which led to the modern one of the director, changed the whole concept of the puppeteer who ceased to be a mere operative becoming instead a creative artist in his or her own right. Increased exposure to other artistic forms, notably the visual arts, also resulted in an increasing divergence of puppetry from mainstream theatre and eventually the puppet theatre, instead of following the actors’ theatre, has come to be a leader in contemporary experimental and alternative theatre.